Challenge Hypothesis 2.0: A Fresh Look at an Established Idea. (24th April 2019) - Goymann, Wolfgang; Moore, Ignacio T; Oliveira, Rui F
Abstract: For male vertebrates, androgens are considered physiological mediators of the trade-off between mating and parenting effort. About 30 years ago, the challenge hypothesis provided a conceptual framework to explain the variation in androgen levels among individuals and species, primarily as a function of male competition and parental care. Initially developed in—and applied to—birds, the challenge hypothesis was rapidly adopted for other vertebrate groups and even insects. Experimental evidence on birds, however, offers limited support for the challenge hypothesis in terms of explaining androgen responses to social challenges from other males. Rather than throwing the baby out with the bathwater, we advance a modified challenge hypothesis 2.0, in which male–female interactions are more important than male–male interactions in mediating rapid changes in plasma androgen concentrations. The predictions we generate are supported by current evidence from birds and can be tested in other animal taxa.